TechTip: Geonetwork, spatial information management software - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Advances in remote sensing and geographic information system (GIS) technology have led to a dramatic increase in the amount of available geographic information - from satellite imagery and spatial databases to interactive maps.